The Effects of an Integrated Writing Task on Undergraduates’ Critical Thinking in English Argumentative Writing - Huiying Diao; Zhencong Liu (Universitas Riau, 2022)
The critical thinking in English writing skills is among the heated discussions in the field of second language writing. Grounded in Paul & Elder's critical thinking model and aided by Critical Thinking Disposition Inventory-Chinese Version (CTDI-CV), the present study explored non-English majors’ critical thinking ability through examining the development of critical thinking in English argumentative writing. The results shows no significant difference in scores of critical thinking between the experimental group and the control group. The English argumentative writing skills between the experimental group and the control group differed significantly. No relationship between the critical thinking and English argumentative writing scores was indicated in the current study.